Disclosure of HIV status between parents and children in Uganda in the context of greater access to treatment - Kyaddondo, David; Wanyenze, Rhoda K.; Kinsman, John; Hardon, Anita (Journal of Social Aspects of HIV/AIDS, 2013)
While disclosure of HIV sero-status is encouraged in the management of the HIV and AIDS epidemic, it remains a challenge, especially among family members. This article examines the moral dilemmas and pragmatic incentives surrounding disclosure of HIV status in contemporary Uganda. Our findings are based on 12 in-depth interviews, 2 focus-group discussions, 6 key informant interviews with AIDS activists, and open-ended responses derived from 148 HIV-positive persons in a quantitative survey. The study was conducted in 2008–2009 in Kampala, Mpigi, and Soroti districts in Uganda. We found both parents and adult children facing dilemmas in disclosure, whether it was parents revealing their own HIV status to their children or the status of their perinatally infected children, or young people infected through sexual intercourse telling their parents. For both groups, there is fear of blame, stigma, discrimination, and shame and guilt related to unsafe sex, while young people also fear loss of privileges. On the other hand, there are practical imperatives for disclosure in terms of gaining access to care, treatment, and material resources. Faced with these dilemmas, HIV-positive people and their families require professional counselling to help them work through the emotional challenges encountered and identify mechanisms of support and coping.
Keywords: HIV status; Parents; Children; Uganda; Treatment